One-pot synthesis of CuO, ZnO, and Ag nanoparticles: structural, morphological, and bactericidal evaluation - Brito, Sabrina da Costa [UNESP]; Malafatti, João Otávio Donizette; Arab, Fernanda Elisa; Bresolin, Joana Dias; Paris, Elaine Cristina; Souza, Clovis Wesley Oliveira de; Ferreira, Marcos David (Taylor & Francis, 2022)
Materials based on metal oxide nanoparticles with antimicrobial properties have been studied as alternatives to silver, seeking a lower cost, toxicity, and inhibition or retarding of microorganism growth. In this context, the present work aimed to investigate the antimicrobial effect of copper oxide (CuONPs) and zinc oxide (ZnONPs) nanoparticles against silver in Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria. The ultrasound method was applied to obtain the nanoparticles in a single and quick step. Antimicrobial activity was verified by the agar diffusion disk test and flask agitation test. The nanoparticles obtained from CuONPs (15 ± 10 nm) and ZnONPs (11 ± 6 nm) showed more significant inhibition for S. aureus. Besides that, CuONPs showed superior antimicrobial activity than AgNPs and ZnONPs in significant concentrations. Thus, the results reinforce the antimicrobial efficiency of silver, but suggest alternatives with a lower cost material, such as CuO and ZnO nanoparticles.
Keywords: Antimicrobial; copper oxide; nanoparticles; silver; ultrasound method; zinc oxide